A cultural criminology of "new" jihad: insights from propaganda magazines - Sunde, Hans Myhre (Crime, media, culture, 2021)
The backgrounds and modus operandi of more recent jihadi terrorists tend to share factors and characteristics more typically associated with non-political violence such as mass-killings and gang violence. Their attacks, moreover, seem to have been precipitated not by the direct instructions of a formal hierarchy but by the encouragement of propaganda produced and disseminated by networked, media-savvy terrorist groups. It is necessary to explain how these ?recruitment? efforts work. Cultural criminology, with its understanding of the relationship between mediated meaning and individual experience, can provide such an analysis. The article presents a qualitative document analysis of 32 propaganda magazines produced by the Islamic State and Al-Qaeda. It demonstrates that they contain significantly more than religious rhetoric and military strategy. Rather, they are part of a process that crystalizes a jihadi subculture that appeals to disaffected and/or marginalized, excitement-seeking youths. The magazines cultivate violence by constructing a militarized style that celebrates outlaw status, where violence is eroticized and aestheticized. They idealize the notion of a jihadi terrorist that is tough and willing to commit brutal violence. The lifestyle portrayed offers the possibility of heroism, excitement, belonging and imminent fame, themes often espoused by conventional, Western consumer culture. The magazines occasionally draw on street jargon, urban music, fashion, films, and video games. The subcultural model of jihadi propaganda we explicate provides a novel way of understanding terrorist recruiting tactics and motivations that are not necessarily in opposition to contemporary conventional criminal and ?mainstream? cultures, but in resonance with them.